Enhancing Health Care in the Veteran Community Through Synergistic Research Funding - Lane, Michelle D.; Lidie, Kristy B.; Santullo, Ray F.; Dalal, Stephen J. (Frontiers in Psychiatry, 2021)
The veteran population faces myriad health burdens, particularly regarding mental health. As veterans age, combined genetic, environmental, and biochemical factors with natural biological processes may increase their susceptibility to mental health disorders as well as neuropsychiatric and dementia-related disorders that present as persistent cognitive impairment. Multi-organizational, multidisciplinary research partnerships help explore relevant evidence-based methodologies and create a two-way continuum between basic science and clinical application to address veterans’, often complex, health care needs. The Congressionally Directed Medical Research Programs (CDMRP), a global funding organization located within the U.S. Army Medical Research and Development Command (USAMRDC), fosters novel approaches to biomedical research in response to the expressed needs of stakeholders and, as directed by Congress, many CDMRP programs focus on topics that are relevant to the health care of veterans. The CDMRP’s foundation as a research management organization includes a two-tier review process and fully integrates consumer advocates. The CDMRP complements the U.S. Department of Veterans Affairs (VA) research through collaborative partnerships and synergistic award mechanisms tailored to areas of greatest need. Continued partnerships between the VA and CDMRP can facilitate translation of basic research to clinical application and enhance health care in the veteran community. This perspective highlights the need for research to address mental health issues affecting the veteran community, describes how the CDMRP integrates veterans into its processes, and discusses how the CDMRP’s processes and collaborations with the VA have the capacity to improve mental health care for veterans.